Penerapan Metode Fuzzy Tsukamoto untuk Menentukan Harga Sewa Hotel (Studi Kasus: Gili Amor Boutique Resort, Dusun Gili Trawangan, Nusa Tenggara Barat) - Rudito Pujiarso Nugroho; Budi Darma Setiawan; M. Tanzil Furqon (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Gili Trawangan is a place that is popular in the lndonesian and foreign traveler. ln the hospitality industry in Gili Trawangan they have 3 seasons, namely; low season, high season, and peak season. Gili Amor Boutique Resort is one of the hotels located on Gili Trawangan that has problem to determining the hotel rental price because they only estimates the hotel price to be rented based on the current season. Based on the problem, Fuzzy Tsukamoto was chosen because it has a monotone logic on each rules, which is each consequence of lF-THEN rules must be represented by a fuzzy set with a monotonus membership function. Fuzzy logic is use to solve periods in an linguistically or variabels that contain uncertainties rather than the numbers. The Tsukamoto Method has 3 stages, namely; fuzzification, fuzzy inference system, and defuzzification. Fuzzification functions to change the crisp value to fuzzy value. Fuzzy inference system are conclusions based on fuzzy rules. Defuzzification is the process of turning fuzzy output into a crisp value using weighted average concept. ln this research, the rules will be searched automatically by the system based on the data that has been inputted. The data that has been inputted will be added â€œeventâ€ to distinguish holidays, significant price, and etc. The result of this research obtained an error using MAPE amounting to 28.41% for data test with Studio type of rooms and 27.85% for data test with Premiere type of rooms.